IMPLEMENTASI GOOD CORPORATE GOVERNANCE DAN HUBUNGANNYA DENGAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ) - Ellyta Muchtar (Cakrawala - Jurnal Humaniora, 2010)
The emergence of corporate governance are both triggered the scandal that happened in the big companies in Indonesia and the United States. This large company in trouble for doing good corporate governance practices that the merger did poorly with several large banks and the government's environmental damage caused as a result of the activities of several companies related to natural resources. In the U.S. corporate governance is poor precisely has been done by the top management as happened in Enron. Goal implementation of corporate governance is good to encourage an efficient market, transparency and consistent with how implementing the principles of good corporate governance are accountability, responsibility, transprancy and fairness. One of the implementation of corporate governance is good through corporate social responsibility. Implementation should be reported by the company in a report called sustainability reporting, and entered in the company's annual report. The Companies that have been carrying out social responsibility indicates that the company has done with good corporate governance. Keywords: Good Corporate governance,the principles of good corporate governance, CSR,  CSR Discloure